An analysis of happiness and resilience in Souvankham Thammavongsa’s How to pronounce knife - Casco-Solís, Sara (International Journal of English Studies, 2025)
This article examines the literary representation of the complexities of the refugee experience in five short stories from Souvankham Thammavongsa’s collection How to pronounce knife. Drawing on Sarah Ahmed’s (2010) notion of happiness, it investigates how the stories expose the harmful effects of neoliberal scripts on refugees’ wellbeing and interpersonal relations. Moreover, it highlights the characters’ refusal to comply with normative expectations that cast refugees primarily through discourses of trauma, pain, or suffering. Instead, Thammavongsa portrays a community of Lao refugees who, by resisting these prescriptive narratives, cultivate affective bonds of care and solidarity. I argue that such practices emerge as forms of relational resilience that challenge erasure and invisibility, offering alternative ways of imagining refugee life beyond dominant representational frameworks.